Development of functional pectin edible films with fillers obtained from red cabbage and beetroot - Otálora González, Carlos Mauricio (2020)
The present study aims to develop through casting, functional composite edible films based on pectin using beetroot powder and red cabbage powder as fillers obtained from by-products of plant tissue industrialisation. Physico-chemical, mechanical, thermal properties and colour stability of the films along 30 days of storage (5–45 °C; absence of light) were evaluated. The moisture and the stress at break decreased, and the intensity of red colour and the hydrophobicity increased with the presence of fillers. According to the FTIR results, there was a good compatibility between matrix and fillers in the composites. Pectin films generated an enhanced stability of red colour after 30 days of storage at 5 and 25 °C and, in general, after 16 days for 45 °C, showing their suitability to be used as colouring agents for edible food packaging applications.